6‐month buprenorphine implant approved. Issue 7 (July 2016) - Unknown
Abstract : In May, the Food and Drug Administration approved Probuphine, the first buprenorphine implant for treatment of opioid dependence. "The safety and effectiveness of Probuphine have not been established in children or adolescents < 16 years of age, " according to the labeling.